Advancing Clinical Psychology With Improved Doctoral Training in Science. - Vrieze, Scott; Elliott, Maxwell; Iacono, William; Klimes-Dougan, Bonnie; Krueger, Robert; Lissek, Shmuel; Luciana, Monica; MacDonald III, Angus W.; Ringwald, Whitney; Siegel, Wayne; Waldman, Irwin; Wilson, Sylia (Training & Education in Professional Psychology, 2026)
Clinical psychology is a young science. Psychological suffering remains extensive, with core scientific issues the subject of ongoing study and debate. Clinical practice depends on the research base for elucidating etiology, systematic improvements in provision of mental health care, improvements in public health, and credibility with clients and the larger public. Science-oriented training programs endeavor to develop students into independent scientists, clinicians, and/or administrators who produce knowledge and translate it to improve clinical care. Existing training standards accommodate programs with a heavy clinical focus and little to no research training. To accelerate scientific progress, these standards must also accommodate increased scientific and research training by reducing generalist requirements and increasing curricular flexibility for students. On net, these changes would allow clinical psychologists more opportunities to work at the level of the clinic, system, policy, or laboratory and thereby accelerate scientific discovery and translation to understand and reduce mental health burdens in our society, all while existing programs, including practitioner-oriented programs, may continue to flourish. Public Significance Statement: Clinical psychology is an applied science, yet science training during graduate school is constrained under present models. This article proposes a set of principles and a training structure that would improve science training.